2009
DOI: 10.4103/0970-0218.51232
|View full text |Cite
|
Sign up to set email alerts
|

Spousal communication, changes in partner attitude, and contraceptive use among the Yorubas of Southwest Nigeria

Abstract: Objective:This paper highlights the relevance of spousal communication on males' attitude towards their partners' contraceptive use.Design:This was a cross-sectional study.Materials and Methods:Data for the study were obtained from a survey carried out in three states, Oyo, Osun, and Ondo, mainly inhabited by the Yorubas.Results:The results show that men have a significant role to play in the adoption of contraception. About 37% of the respondents reported joint decision making on when to have another child, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 12 publications
(14 reference statements)
3
47
0
1
Order By: Relevance
“…In 1994, based on emerging evidence, the International Conference on Population and Development encouraged public health authorities to address barriers to contraceptive use created by gender dynamics that may keep men from being actively involved or may negatively influence contraceptive decision-making and use among couples (United Nations [UN], 1994). Recent quantitative studies in rural and urban Nigeria found that men were generally not involved in FP decision-making despite their partners' wishes (Ijadunola et al, 2011;Ogunjuyigbe, Ojofeitimi, & Liasu, 2009;Utoo, Mutihir, & Utoo, 2010). Other qualitative studies from rural Tanzania also demonstrate that although men dominate several aspects of social life, they do not participate in decision-making around childbearing (Keele, Forste, & Flake, 2005, Wight, Plummer, & Ross, 2012.…”
Section: Introductionmentioning
confidence: 90%
“…In 1994, based on emerging evidence, the International Conference on Population and Development encouraged public health authorities to address barriers to contraceptive use created by gender dynamics that may keep men from being actively involved or may negatively influence contraceptive decision-making and use among couples (United Nations [UN], 1994). Recent quantitative studies in rural and urban Nigeria found that men were generally not involved in FP decision-making despite their partners' wishes (Ijadunola et al, 2011;Ogunjuyigbe, Ojofeitimi, & Liasu, 2009;Utoo, Mutihir, & Utoo, 2010). Other qualitative studies from rural Tanzania also demonstrate that although men dominate several aspects of social life, they do not participate in decision-making around childbearing (Keele, Forste, & Flake, 2005, Wight, Plummer, & Ross, 2012.…”
Section: Introductionmentioning
confidence: 90%
“…Men's disapproval has been found to work through direct opposition and also through poor communication between couples about FP and fertility goals. Spousal communication and joint decisionmaking have been associated with increased contraceptive use (Oheneba-Sakyi and Takyi 1997;Feyisetan 2000;Kaggwa, Diop, and Storey 2008;Ogunjuyigbe, Ojofeitimi, and Liasu 2009;Hartmann et al 2012). In Malawi, women who discussed FP with their spouses were over six times more likely to use FP (Ntshebe 2011).…”
Section: Studies In Family Planning 46(2)mentioning
confidence: 99%
“…Besides determining the effects of individual traits on contraceptive use, some research has been conducted to identify the effects of relationship-level factors, such as the husband and wife's fertility desires and reported communication, on contraceptive use 21-25 . Some couple studies conducted in Nigeria and Pakistan noted that women tend to use contraception when their husbands are satisfied with the number of children they have 23,25 . Another study using Kenya 1989 and 1993 DHS data found that women were twice as likely to use contraception if their husband truly desired no more children than when they alone felt so (39.2% vs. 23.2%) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted across Africa and South Asia have suggested that communication about fertility and contraception between spouses is important as it encourages contraceptive use and results in smaller family sizes 25,28-36 . For example, a study of the Kenya 1993 DHS data from 1257 couples found that couples where both partners reported discussing FP were more likely to be ever-users of FP though the relationship may go in the other direction with ever users more likely to discuss FP 37 .…”
Section: Introductionmentioning
confidence: 99%